Simulation of Craniectomy Size in Decompressive Craniectomy for Ischaemic Stroke - Aina Najwa, Nadzri; Mohd Jamil Mohamed, Mokhtarudin; Wan Naimah, Wan Ab Naim; Payne, Stephen J. (Springer, 2022)
Decompressive Craniectomy (DC) surgery is recommended to treat patients who suffered from large ischaemic cerebral infarction. Although DC surgery has been proven to reduce intracranial pressure (ICP) within the skull, too large of DC opening may contribute to risk of tissue injury. Computational studies nowadays are very useful in predicting and decision making, especially in clinical studies. Therefore, a simulation was performed using mathematical modeling on an idealized 3D brain model to evaluate the outcome of different skull opening sizes in DC towards treating the brain tissue swelling in ischaemic stroke. The model is simulated based on poroelastic theory and capillary filtration. Our results show that larger craniectomy size may reduce the midline shift of the ventricle due to swelling tissue. Nevertheless, the bulging of swollen tissue out from the skull opening causes a little amount of stress applied at the edges of the opening. This modelling work may be used for further research in further research in evaluating the suitable craniectomy size for DC.